The Central Variant of Posterior Reversible Encephalopathy Syndrome: A Systematic Review and Meta-Analysis - Bahadar S. Srichawla; Maria A. Garcia-Dominguez; Brian Silver (Neurology International)
Background: The central variant of posterior reversible encephalopathy syndrome (cvPRES) is an atypical subtype of PRES. Although no unifying definitions exists, it is most often characterized by vasogenic edema involving “central” structures, such as the brainstem, subcortical nuclei, and spinal cord, with relative sparing of the parieto-occipital lobes. Methods: This systematic review and meta-analysis followed the PRISMA guidelines and was pre-registered on PROSPERO [CRD42023483806]. Both the Joanna Briggs Institute and New-Castle Ottawa scale were used for case reports and cohort studies, respectively. The meta-analysis was completed using R-Studio and its associated “metafor” package. Results: A comprehensive search in four databases yielded 70 case reports/series (n = 100) and 12 cohort studies. The meta-analysis revealed a pooled incidence rate of 13% (95% CI: 9–18%) for cvPRES amongst included cohort studies on PRES. Significant heterogeneity was observed (I2 = 71% and a τ2 = 0.2046). The average age of affected individuals was 40.9 years, with a slightly higher prevalence in males (54%). The most common etiological factor was hypertension (72%). Fifty percent had an SBP >200 mmHg at presentation and a mean arterial pressure (MAP) of 217.6 ± 40.82. Imaging revealed an increased T2 signal involving the brain stem (88%), most often in the pons (62/88; 70.45%), and 18/100 (18%) cases of PRES with spinal cord involvement (PRES-SCI). Management primarily involved blood pressure reduction, with adjunctive therapies for underlying causes such as anti-seizure medications or hemodialysis. The MAP between isolated PRES-SCI and cvPRES without spinal cord involvement did not show significant differences (p = 0.5205). Favorable outcomes were observed in most cases, with a mortality rate of only 2%. Conclusions: cvPRES is most often associated with higher blood pressure compared to prior studies with typical PRES. The pons is most often involved. Despite the severity of blood pressure and critical brain stem involvement, those with cvPRES have favorable functional outcomes and a lower mortality rate than typical PRES, likely attributable to reversible vasogenic edema without significant neuronal dysfunction.